2004
DOI: 10.1079/bjn20041174
|View full text |Cite
|
Sign up to set email alerts
|

Thermally oxidised sunflower-seed oil increases liver and serum peroxidation and modifies lipoprotein composition in rats

Abstract: Peroxidation of LDL and other lipoproteins is thought to play a central role in atherogenesis. Dietary thermally oxidised oils may increase atherogenic risk in consumers by increasing their oxidative status. The present paper compares the effects of two diets containing unused sunflower-seed oil (US) or sunflower-seed oil repeatedly used in frying (FS) (both 15 g/100 g diet) on weight gain, food efficiency ratio, serum lipid levels and lipoprotein composition, and the content of thiobarbituric acid-reactive su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 33 publications
6
38
0
1
Order By: Relevance
“…This is why the origin and amount of oil fed to animals ad libitum are important factors. Most of academic studies [4][5][6][7][8][9] on used frying oil mixed 12-20 wt% of thermally oxidized oil in the diet corresponding to the oil contents in an ideal human diet. As the optimum oil content in a rat diet is 4-7 wt%, that for humans seems inapplicable to rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why the origin and amount of oil fed to animals ad libitum are important factors. Most of academic studies [4][5][6][7][8][9] on used frying oil mixed 12-20 wt% of thermally oxidized oil in the diet corresponding to the oil contents in an ideal human diet. As the optimum oil content in a rat diet is 4-7 wt%, that for humans seems inapplicable to rats.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggest that ingestion of recovered oil did not produce notable changes in oil absorption from the small intestine or metabolism in the liver. Garrido-Polonio et al 9) carried out an experiment in which growing Wistar rats weighing 65 g were fed for 27 days a diet containing 15% sunflowerseed oil repeatedly used in frying (PC 27.7%, oligomer content 16.6%). The HDL fraction of the experimental rats had significantly increased levels of total and esterified cholesterol and phospholipids.…”
mentioning
confidence: 99%
“…Consistent with the results of the current study, Kamsiah et al (23) showed that after 20 weeks of consumption of 5 times-heated palm oil, LDL-C levels increased, yet no significant change in HDL-C levels was observed. In this context, Garrido Polonio et al (24) showed that negative alterations in lipid profile of rats fed heated sunflower oil may be due to decreased intake of unsaturated fatty acids, especially linoleic acid. Changes in lipid profile following consumption of heated oil could increase atherosclerosis risk as indicated by Adam et al (25).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of used frying oil on living body have been investigated by giving the oil as is to animals 18,19) . In accordance with the oxidation level of the oil, not only cytotoxicity but also gross symptoms, such as seborrhea, diarrhea, polyuria, excessive hair loss and so forth were observed.…”
Section: Discussionmentioning
confidence: 99%